Gerhardtia tomentosa and Ossicaulis borealis (Agaricales, Lyophyllaceae)—Two new species from northeast China - Yue Qi; Fei Xu; Zhao-Qian Yang; Jian-Xuan Hou; Ai-Guo Xu; Hong-Bo Guo; Xiao-Dan Yu; Rui-Heng Yang (Frontiers in Microbiology, 2023)
BackgroundGerhardtia and Ossicaulis are two genera within the family Lyophyllaceae, which show an apparently poor species diversity worldwide. During the field investigation on wild macrofungi, six interesting collections within Gerhardtia and Ossicaulis genera are discovered in the northeastern China.MethodsTo identify whether these collections of Gerhardtia and Ossicaulis are novel species, we performed phylogenetic analyzes using the following DNA regions: the internal transcribed spacer (ITS) region and the large subunit nuclear ribosomal RNA (nrLSU) region. Moreover, a traditional morphological method also be conducted based on both the macro-morphological and micro-morphological features.ResultsThe results indicated that these collections tested formed two independent lineages in each genus with a high support. In addition, they can easily be separated from all other taxa of the two genera in morphology. Based on the combination of morphological and molecular data, Gerhardtia tomentosa and Ossicaulis borealis, are confirmed as two new species to science.DiscussionsThis study provided a theoretical basis is for the two lyophylloid genera and indicated that the biodiversity resources of northeastern China might be underestimated.